THE EXISTENCE OF MUI TV IN BROADCASTING DA'WAH THROUGH YOUTUBE MEDIA - Gunawan, Asep; Andini, Diong; Ranawigena, Ghaitsa; Purnama, Dwi Rahmawati; Zakiyah Harsyah, Fathiyah; Luse Tokan, Alvares; Firmansyah, Adit; Mulmuttaqin, M. Imam (Abdi Dosen : Jurnal Pengabdian Pada Masyarakat, 2023)
The digital era gave to a new era in society, the transfer of media from electronic to digital makes it easier for humans to access various information. YouTube is one of the media that is quite loved by the people of Indonesia, the decline in public consumption of conventional television is because one of them is that people have switched to digital media such as YouTube. Digital da'wah is currently a trend, because most people are looking for information and knowledge from new media such as YouTube. Da'wah through the media YouTube is currently widely found, the delivery of da'wah is also increasingly diverse and the targeted mad'u is wider without being limited by space and time. The method used in this study is a qualitative approach while data collection is obtained by observation and interviews. The results of this study are The use of YouTube as a propaganda medium in the modern era is indeed effective, compared to other applications or television. Apart from being able to watch it anytime and anywhere, YouTube content tends to be presented in a relaxed manner. Especially today, we see a lot of the podcast phenomenon mushrooming in society. This also prays for the preachers to make studies. However, packaged in a podcast style.